Gunnar Myrdal and Asian drama in context - Kanbur, Ravi (London, 2018)
"This paper attempts to understand Asian Drama in the context of the development debates of its time, and in terms of the sensibilities that Gunnar Myrdal-the brilliant economic theorist and philosopher of knowledge, and the Swedish politician-brought to the conceptualization of the problems and prospects of development. The paper covers: (i) what Gunnar Myrdal brought to the analysis of development from his long, varied and distinguished academic and practitioner career; (ii) the development terrain in the mid-twentieth century; and (iii) how Asian Drama lay on that terrain and in the remaining years of Gunnar Myrdal's continued eventful life. The two central questions posed in the paper are: (i) How did Gunnar Myrdal's broad experience and perspective influence Asian Drama? (ii) How did Asian Drama influence the development debate?"